ANALISIS PERBANDINGAN PENERAPAN PENGENDALIAN BAHAN BAKU POLYPROPYLENE DAN LOW DENSITY POLYETHYLENE MENGUNAKAN MODEL EOQ DAN JIT/EOQ UNTUK MENGETAHUI TINGKAT PERSEDIAAN YANG EFEKTIF PADA PT XYZ - Safri, Safri (Feb Universitas Dirgantara Marsekal Suryadarma, 2023)
So far, inventory control for PP and LDPE products Supprise Kapsul at PT XYZ has been carried out with the assumption that practitioners are not academics, with an average approach of the last three months. For this reason, the researchers implemented raw material inventory control using the EOQ and JIT/EOQ methods.By using the evaluative research method, the research sample is in the form of operational control of raw materials, the type of data is in the form of documentation, the data source is primary data obtained through observation and interviews, and secondary data in the form of transaction evidence, notes, reports on raw material supplies.The results showed that the economic cost using the EOQ method was 18,603 Kg and the JIT/EOQ method was 55,330 Kg. With an average order for PP raw materials the EOQ method is 18 times and JIT/EOQ is 6 times. The average order for LDPE raw materials using the EOQ method is 11 times and JIT/EOQ is 6 times. The JIT/EOQ method is more economical than the EOQ method at a maximum capacity of 480 PP units and 60 LDPE units. Costs that can be saved in 1 year on PP materials are Rp. 175,068,594 and can save costs in 1 year for LDPE materials of Rp. 14,692,787Â Keywords: EOQ, JIT, Inventory control